Precise account of frictional loads in motor current-based compensation system of cutting force-induced error - Turyagyenda, G.; Yang, J.; Wu, H. (Journal of Mechanical Engineering Science, 2007)
The balance between precision and its cost implications is a major determining factor for the competitiveness in the contemporary machining industry. The current paper presents an inexpensive compensation system for cutting force induced error based on current sensory system for indirect monitoring of cutting force. Based on machining parameters and online sensor signal, a dedicated model predicts the corresponding error. The model precisely accounts for the complex phenomena of coulomb and viscous frictions in the transmission system. Finally, the predicted error is compensated by means of external shifting of respective coordinate system origins in real-time. This system is convenient and reliable and, in addition, precise and easy to repair. The experimental evaluation of the system demonstrated robustness and great enhancement of machine accuracy.
Keywords: modelling; viscous friction; cutting force-induced error; Coulombic friction